Characterization of β-adrenergic receptors in the heart chambers of adult turkeys. Issue 3 (June 2015) - Hoffmann, Sandra; Müller, Torsten; Abraham, Getu
Highlights β-Adrenergic receptors are equally distributed in turkey hearts. β-Adrenergic receptor density is age-dependent. The β1-adrenergic receptor subtype was exclusively present in all four cardiac chambers.